2017
DOI: 10.1186/s12906-017-1722-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of use of complementary and alternative medicine by hypertensive patients attending primary health care facilities in Kinshasa, Democratic Republic of the Congo: a cross-sectional study

Abstract: BackgroundIn the Democratic Republic of the Congo the control of hypertension is poor, characterized by an increasing number of reported cases of hypertension related complications. Poor control of hypertension is associated with non-adherence to antihypertensive medication. It is well established that the use of complementary and alternative medicine is one of the main factors of non-adherence to antihypertensive medication. The aim of this study is to determine the prevalence and factors associated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
0
12
3
Order By: Relevance
“…This study highlighted the prevailing high percentage use of CAM among our Saudi respondents (61.6%), which is significantly higher than the rates reported by previous studies 9,[11][12][13][14] and lower than that reported by Abuelgasim et al 5 However, in contrast to the previous studies, our study was conducted among the general population visiting the primary care clinics irrespective of whether they have chronic medical conditions (including cancer). Our reported rate would have been different if we had delved further into the existing medical conditions of our patients.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…This study highlighted the prevailing high percentage use of CAM among our Saudi respondents (61.6%), which is significantly higher than the rates reported by previous studies 9,[11][12][13][14] and lower than that reported by Abuelgasim et al 5 However, in contrast to the previous studies, our study was conducted among the general population visiting the primary care clinics irrespective of whether they have chronic medical conditions (including cancer). Our reported rate would have been different if we had delved further into the existing medical conditions of our patients.…”
Section: Discussioncontrasting
confidence: 68%
“…11 In Saudi Arabia, approximately 69.9% of the population with cancer use CAM. 5 CAM use was also reported to be 29.9% in Lebanese adults, 12 26.1% among hypertensive patients in Congo, 9 47.9% among cancer patients in Mongolia, 13 and 43.4% among cardiovascular patients in Singapore. 14 Several studies have demonstrated the efficacy and safety of CAM for certain medical problems.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In Australia, however, similar to the present study, females with hypertension were generally less likely to consult with CAM practitioners and less likely to use self-prescribed CAM. 11 …”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 Other reports have shown that various CMs are used to treat hypertension in the US, Europe, Australia, Nigeria, and Congo. 7 , 8 , 9 , 10 , 11 In Taiwan, 337 types of powdered herbal preparations are covered by national insurance and are prescribed for chronic disease, including hypertension patients. 12 , 13 On the other hand, traditional Korean Medicine (KM) used in the Republic of Korea focuses mainly on neurological and musculoskeletal disorders rather than chronic diseases, including hypertension.…”
Section: Introductionmentioning
confidence: 99%